2018
DOI: 10.3892/etm.2018.6831
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic treatment after computer‑controlled compression in minipig: A preliminary report on the effect of epidural�vs.�direct spinal cord cooling

Abstract: The aim of the present study was to investigate the therapeutic efficacy of local hypothermia (beginning 30 min post-injury persisting for 5 h) on tissue preservation along the rostro-caudal axis of the spinal cord (3 cm cranially and caudally from the lesion site), and the prevention of injury-induced functional loss in a newly developed computer-controlled compression model in minipig (force of impact 18N at L3 level), which mimics severe spinal cord injury (SCI). Minipigs underwent SCI with two post-injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“… 17 Gedrova and colleagues created a 20-point scale where 1–8 represent slight or extensive movement for each individual joint of the hindlimbs, 9–11 represent sweeping and the ability to get up by itself (though without the ability to maintain balance), and 12–20 characterize the ability to walk a few steps without forelimb/hindlimb coordination to consistent stepping. 49 , 50 Santamaria and colleagues developed the Miami Porcine Walking Scale, a 10-point scale based on hindlimb stepping and weight bearing with 1 corresponding to complete paraplegia and 10 indicating no apparent deficit. 9 , 26 The Tarlov scale, used by Zurita and colleagues, is a similar 10-point scale of hindlimb motor function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 17 Gedrova and colleagues created a 20-point scale where 1–8 represent slight or extensive movement for each individual joint of the hindlimbs, 9–11 represent sweeping and the ability to get up by itself (though without the ability to maintain balance), and 12–20 characterize the ability to walk a few steps without forelimb/hindlimb coordination to consistent stepping. 49 , 50 Santamaria and colleagues developed the Miami Porcine Walking Scale, a 10-point scale based on hindlimb stepping and weight bearing with 1 corresponding to complete paraplegia and 10 indicating no apparent deficit. 9 , 26 The Tarlov scale, used by Zurita and colleagues, is a similar 10-point scale of hindlimb motor function.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothermia has been explored as another anti-inflammatory tool by reducing metabolic consumption, energy demands, local edema, and oxidative stress. 49 , 50 Once again, studies on the porcine model have shown mixed efficacy. Gedrova and colleagues found that local hypothermia improved hindlimb recovery in mild SCI, but not in severe injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various therapeutic measures, such as hypothermia, neuroprotective drugs, genetic manipulation of intraspinal plasticity, or reparative strategies, have been proposed to ameliorate, suppress, or reverse the activity of numerous negative factors contributing to the expansion of necrosis, and accentuating the tissue damage within the secondary phase of SCI. 61 62 63 64 65 66 …”
Section: Management Of Autonomic Dysreflexiamentioning
confidence: 99%
“…In our previous experiment, we studied the effects of local hypothermia on selected parameters in a minipig model of contusion SCI using a computerized compression device. In this model we were able to scale the impact strength (8N, 15N, 18N) and thus compare the findings for varied degrees of contusion (Gedrova et al, 2018;Zavodska et al, 2018). In the control (normothermic) group, the graded lesion at the impact site was recorded as 47% loss of tissue with a force of 8N impact, 67% loss of tissue with a force of 15N impact and 79% loss of tissue with a force of 18N impact after 9 weeks of survival.…”
Section: Local Hypothermiamentioning
confidence: 99%